Electrocardiographic Predictors of Heart Failure With Reduced Versus Preserved Ejection Fraction: The Multi‐Ethnic Study of Atherosclerosis. Issue 6 (June 2017) - O'Neal, Wesley T.; Mazur, Matylda; Bertoni, Alain G.; Bluemke, David A.; Al‐Mallah, Mouaz H.; Lima, Joao A. C.; Kitzman, Dalane; Soliman, Elsayed Z.
Abstract : Background: Several markers detected on the routine 12‐lead ECG are associated with future heart failure events. We examined whether these markers are able to separate the risk of heart failure with reduced ejection fraction (HFrEF) from heart failure with preserved ejection fraction (HFpEF). Methods and Results: We analyzed data of 6664 participants (53% female; mean age 62±10 years) from MESA (Multi‐Ethnic Study of Atherosclerosis) who were free of cardiovascular disease at baseline (2000–2002). A competing risks analysis was used to compare the association of several baseline ECG predictors with HFrEF and HFpEF detected during a median follow‐up of 12.1 years. A total of 127 HFrEF and 117 HFpEF events were detected during follow‐up. In a multivariable adjusted model, prolonged QRS duration, delayed intrinsicoid deflection, left‐axis deviation, right‐axis deviation, prolonged QT interval, abnormal QRS‐T axis, left ventricular hypertrophy, ST/T‐wave abnormalities, and left bundle‐branch block were associated with HFrEF. In contrast, higher resting heart rate, abnormal P‐wave axis, and abnormal QRS‐T axis were associated with HFpEF. The risk of HFrEF versus HFpEF was significantly differently for delayed intrinsicoid deflection (hazard ratio: 4.90 [95% confidence interval (CI), 2.77–8.68] versus 0.94 [95% CI, 0.29–2.97]; comparison P =0.013), prolonged QT interval (hazard ratio: 2.39 [95% CI, 1.55–3.68] versus 0.52 [95% CI, 0.23–1.19]; comparison P <0.001), and ST/T‐wave abnormalities (hazard ratio: 2.47 [95% CI, 1.69–3.62] versus 1.13 [95% CI, 0.72–1.77]; comparison P =0.0093). Conclusions: Markers of ventricular repolarization and delayed ventricular activation are able to distinguish between the future risk of HFrEF and HFpEF. These findings suggest a role for ECG markers in the personalized risk assessment of heart failure subtypes.